1983
DOI: 10.1128/iai.41.3.1089-1098.1983
|View full text |Cite
|
Sign up to set email alerts
|

Serological evaluation of O fever in humans: enhanced phase I titers of immunoglobulins G and A are diagnostic for Q fever endocarditis

Abstract: Serological parameters were compared in 15 cases of Coxiella burnetii infection comprising 5 cases each of primary Q fever, chronic granulomatous hepatitis, and endocarditis. The diagnosis was made on the basis of clinical history and serology and on the isolation of C. burnetii phase I from biopsy specimens of liver and bone marrow from two patients with granulomatous hepatitis and from the aortic valve vegetations of five patients with endocarditis. The temporal sequences of immunoglobulin levels, rheumatoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
97
0
2

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(103 citation statements)
references
References 32 publications
(47 reference statements)
4
97
0
2
Order By: Relevance
“…All these sera were frozen and transferred to our laboratory within a few days after venipuncture, and were stored at -30 C before examination. The indirect immunofluorescence (IF) test was used to detect antibodies against phase I and phase II antigens of C. burnetii (16). As a screening test, all sera were diluted 40-fold with phosphate-buffered saline containing 0.3% ovalbumin (Sigma Chemicals Co., St. Louis, Mo., U.S.A.).…”
mentioning
confidence: 99%
“…All these sera were frozen and transferred to our laboratory within a few days after venipuncture, and were stored at -30 C before examination. The indirect immunofluorescence (IF) test was used to detect antibodies against phase I and phase II antigens of C. burnetii (16). As a screening test, all sera were diluted 40-fold with phosphate-buffered saline containing 0.3% ovalbumin (Sigma Chemicals Co., St. Louis, Mo., U.S.A.).…”
mentioning
confidence: 99%
“…In Q-fever infections, C. burnetii may not be circulating in the blood but may be present in other tissues such as bone marrow, as demonstrated in patients with chronic Q fever (Peacock et al 1983) and post-Q-fever fatigue syndrome 5 years after the primary infection (Harris et al 2000) and 12 years following acute infection (Marmion et al 2005). In a previous study, dilutions of the vaccine Q-Vax Ò (containing approximately 1 · 10 9 cells per 25 lg) were made in buffer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in chronic Q fever, C. burnetii DNA is present in bone marrow samples (Peacock et al 1983) in which it can persist for up to 12 years after primary infection (Harris et al 2000;Marmion et al 2005). Bone marrow has similar inhibitors as blood with an increased amount of host (eukaryotic) DNA, which is itself inhibitory to PCR (Roussel et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, IFA is the reference technique for Q-fever diagnosis [25], and the InoDiag technology described here offers the advantage of IFA with automation. As for acute F. tularensis infection, because of the difficulty of culturing the pathogen, most of the cases are diagnosed on the basis of combined clinical and serological findings.…”
Section: Discussionmentioning
confidence: 99%